Development of UV-curable ZrO2 slurries for additive manufacturing (LCM-DLP) technology. Issue 13 (October 2019) - Borlaf, Mario; Serra-Capdevila, Albert; Colominas, Carles; Graule, Thomas
Abstract: Digital Light Processing (DLP) is a powerful technique for the preparation of ceramic parts with high resolution and complex shapes. In the last years, the development of photosensitive slurries for the production of ceramics with good mechanical properties has received much attention. In this work, ZrO2 UV-curable slurries were prepared in two steps for their application in DLP. Firstly, the surface modification of the ZrO2 particles was carried out using a dispersing agent and secondly, the modified powder was dispersed in an acrylate based mixture. Parts with different geometries were printed and a resolution experiment was also carried out in order to determine the limitations of the slurry. Finally, 30 bars were produced to study the mechanical properties of the sintered parts (ρ = 6.00 ± 0.01 g/mL) by 4-point bending tests and Weibull analysis, obtaining a flexural strength σ0 = 741 (718–765) MPa with a Weibull coefficient of 11.4.